Work-related musculoskeletal disorders, fatigue and stress among gas station workers in China: a cross-sectional study - Jing Wang; Andrew Paul Smith; Jialin Fan; Xiaotong Tan (BMJ Open)
Introduction Work-related musculoskeletal disorders (WMSDs) are disorders of the musculoskeletal system that have the highest prevalence among workers worldwide. Workers in gas stations usually work in poor ergonomic working conditions, including prolonged standing and repetitive posturing.Objective The study aimed to investigate the prevalence of WMSDs and fatigue and to identify the predictors of WMSDs among gas station workers.Design The present study was a cross-sectional study.Setting and participants 2962 gas station workers from an oil and gas company in China, with ages ranging from 17 to 75 years old, 55.47% female.Results The prevalence of WMSDs within the 12 months prior to the study was 73.23%, with the highest prevalence in the neck, shoulders, ankles and feet. Furthermore, a correlation was observed between fatigue, stress and WMSDs. Fatigue and job role were the strongest predictors of WMSDs, with an OR range of 2.211–3.413.Conclusions This research identified the detrimental impact of WMSDs and fatigue on gas station workers, indicating the critical need for interventions to reduce WMSDs and relieve fatigue.